Clinical Course May Be Independent from Neuroimaging in DEPDC-5-Related Epilepsy - Bartolini, Emanuele; Della Vecchia, Stefania; Biagioni, Tommaso; Montanaro, Domenico; Ferrari, Anna Rita (Neuropediatrics, 2023)
DEPDC5 is an upstream repressor of the mechanistic target of rapamycin pathway via the GATOR-1 complex. Pathogenic variants causing loss of function typically result in familial focal epilepsy with variable foci. Neuroimaging may either be normal or show brain malformations. Lesional and nonlesional cases may be present within the same family. Here, we describe a parent–child dyad affected by a truncating DEPDC5 pathogenic variant (c.727C > T; p.Arg243*), analyze the epilepsy clinical course, and describe neuroimaging characteristics from a 3T brain magnetic resonance imaging. Despite sharing the same variant, patients diverged both in terms of epilepsy severity and neuroimaging features. Surprisingly, the mother is still suffering from drug-resistant seizures and has normal neuroimaging, while the child has been experiencing prolonged seizure freedom notwithstanding a bottom-of-sulcus focal cortical dysplasia. An increasing gradient of severity has been proposed for families with GATOR1-related epilepsies. We confirm clinical and neuroradiological expressivities are variable and also suggest the prognostication of epilepsy outcome may be particularly difficult. The epilepsy outcome could partially be independent from brain structural abnormalities.
Keywords: mTOR; brain MRI; seizures; focal cortical dysplasia; germinal variants; pathogenic variants